Helicobacter Pylori in Patients with Chronic Immune Thrombocytopenic Purpura: A Pilot Study - Randa Darwish Mohamed; Doaa Mohamed Gaith; Marwa Abd Elhady (Pediatric Sciences Journal)
Background: Chronic immune thrombocytopenic purpura (ITP) is an autoimmune disorder. Children with chronic ITP were reported to be at higher risk of associated Helicobacter pylori (H. pylori) infection. Aim of the work: To identify the frequency of H. pylori infection among children with chronic ITP. Subjects and Methods: This cross-sectional observational study included 70 children with chronic ITP and a control group consisted of healthy 60 children of similar age and sex. They all underwent enzymatic immunoassay (EIA) stool antigen test (SAT) for H. pylori. Results: The group with chronic ITP included 40 (57.1%) males and 30 (42.9%) females, while the control group included 30 (50%) males and 30 (50%) females (p=0.47). The mean ± SD age of the cases and control group was 10.5 ± 6.5 years and 10.3 ± 4.2years (p=0.44). The mean ± SD duration of ITP was 15.8 ± 5.6 months. All patients were on corticosteroid therapy. Only 10 (14.3%) of the cases with ITP underwent splenectomy. There was no statistical difference in the rates of H. pylori among those with ITP and the control group. Among the 70 children with a chronic ITP, 20 (28.6 %) had H. pylori, compared to 11 (19%) of the control group (p=0.172). The rate of H. pylori infection correlated with longer duration of ITP (p-value = 0.03). Conclusion: Despite an apparent increase in rate of H. pylori among those with chronic ITP compared to the control group, it did not mount to statistical significance. Children with chronic ITP do not seem to be more vulnerable than their healthy peers to H. pylori. Further studies of the effect of H. pylori treatment on chronic ITP are recommended.